Особенности внедрения мероприятий по снижению потерь электрической энергии на действующих предприятиях - Овчаренко, Татьяна Ивановна; Васюченко, П. В. (НТУ "ХПИ", 2012)
В статье рассмотрены особенности комплексной политики энергосбережения за счет внедрения мероприятий по снижению потерь электрической энергии в электрических сетях действующих промышленных предприятий. Проанализированы особенности расчета потерь электрической энергии с учетом различных факторов

In the article the features of complex policy of economy of energy due to introduction of measures are considered on the decline of losses of electric energy in the electric networks of operating industrial enterprises. The features of calculation of losses of electric energy are analysed taking into account different factors
Features of introduction of measures on the decline of losses of electric energy on operating enterprises
Keywords: электрооборудование; коэффициент износа; загрузка; сети; трансформатор; напряжение; кабельные линии; мероприятия